Indonesian Sharia Bank KUR Innovation Through A Digital Platform - Kartika Marella Vanni; Tria Noviani (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
The ease of transactions at financial institutions has now been facilitated by the existence of technology that is updated on an ongoing basis. This is also what makes Islamic banking innovate on its products, one of which makes people's business credit (KUR) sharia accessible through a digital platform in collaboration with the telecommunications service company